Consensus Statement of Cardiac Society of Nepal on Diagnosis, Management and Prevention of Acute Rheumatic Fever and Rheumatic Heart Disease in Nepal - Sharma, Deewakar; Prajapati, Dipanker; Shakya, Urmila; Shrestha, Manish; Shakya, Samir; Gautam, Navin Chandra; Manandhar, Reeju; Sherpa, Kunjang; KC, Man Bahadur; Regmi, Prakash Raj; Poudel, Chandra Mani; Adhikari, Chandra Mani; et al. (Nepalese Heart Journal, 2022)
The prevalence of rheumatic heart disease is still significant in Nepal, especially in rural areas. It is an important preventable cause of morbidity and mortality in children and young adults. Diagnosis of rheumatic heart disease and acute rheumatic fever is based on clinical, laboratory, and echocardiographic criteria. Diagnosis and management criteria need to be locally relevant and practical to our context for implementation at the national level. The Cardiac Society of Nepal initiated the development of consensus document with aim of providing a reasonable and practical format of diagnostic and management. We hope this document will be helpful for physicians, pediatricians and cardiologists of the country to diagnose and treat acute rheumatic fever and RHD.